Potency of Green Cincau Leaves (Premna oblogifolia merr) Juice as Prebiotics and its Effect on Laying Hen Performances - Lidiyawati, Anna; Widodo, Eko; Sudjarwo, Edhy (Graduate School, Universitas Brawijaya, 2015)
This study investigated the potency of green cincau leaves (Premna oblongifolia merr) juice as prebiotics end its effect on laying performances (feed intake, egg weight, feed conversion and hen day production) based on pH and digestive viscosity. The potency of green cincau leaves juice as prebiotic was tested. The result showed that green cincau leaves juice was effectively support growth of Lactic Acid Bacteria (LAB) with 4.3 x 102 CFU.g-1 samples but did not support the growth of Escherichia coli. The effect of green cincau leaves juice on laying performances was examined. Two hundred fifty 56-wk-old Hisex Brown layers received different diets namely 0, 5, 7.5, 10 and 12.5 ml of green cincau leaves juice added in the basal feed. The method used in this study was experiment based on Completely Randomized Design and followed by Duncanâ€™s Multiple test if significant effect occurs. The result showed that increase level of P. oblongifolia merr in feed did not significantly affect (P>0.05) feed intake, egg weight, feed conversion and hen day production.Keywords: feed additives, laying hens performance, prebiotic, Premna Â oblongifolia merr juice.